2013
DOI: 10.4315/0362-028x.jfp-13-118
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mentha spicata L. and Artemisia campestris Extracts on the Shelf Life and Quality of Vacuum-Packed Refrigerated Sardine (Sardina pilchardus) Fillets

Abstract: The present study investigated the effects of ethanolic extracts obtained from Mentha spicata and Artemisia campestris on the shelf life and the quality of vacuum-packed sardine fillets stored at 3 ± 1°C for a period of 21 days. The three groups were tested were VC, control group; VM, group treated with 1 % mint extract; and VA, group treated with 1 % artemisia extract. The observed shelf life of sardine fillets was 10 days for control samples, whereas the combination of vacuum packaging with mint and artemisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…Similar findings with rosemary extracts were reported in vacuum packed mackerel burgers (Ucak et al 2011) and with turmeric extract in vacuum packed rainbow trout steaks (Pezeshk et al 2011) during chill storage. In a similar study, Houicher et al (2013) also observed lower TVB-N values in mint extract treated vacuum packed sardine fillet compared to vacuum packed sardine alone. It is well known that the complete removal of oxygen from the pack inhibits the aerobic bacterial growth and the result from present study suggests that combined use of vacuum packaging and mint extract further inhibits the microbial growth; thereby maintains lower TVB-N levels in fish during storage.…”
Section: Tvb-nmentioning
confidence: 52%
See 4 more Smart Citations
“…Similar findings with rosemary extracts were reported in vacuum packed mackerel burgers (Ucak et al 2011) and with turmeric extract in vacuum packed rainbow trout steaks (Pezeshk et al 2011) during chill storage. In a similar study, Houicher et al (2013) also observed lower TVB-N values in mint extract treated vacuum packed sardine fillet compared to vacuum packed sardine alone. It is well known that the complete removal of oxygen from the pack inhibits the aerobic bacterial growth and the result from present study suggests that combined use of vacuum packaging and mint extract further inhibits the microbial growth; thereby maintains lower TVB-N levels in fish during storage.…”
Section: Tvb-nmentioning
confidence: 52%
“…Antioxidant extracts from Mentha spp. has been used to control lipid peroxidation in different food systems including sunflower oil, lamp, pork and chilled fish (Kanatt et al 2007;Biswas et al 2012;Houicher et al 2013). The result of present study revealed that inhibitory effects of vacuum can be further enhanced by mint extract treatment.…”
Section: Pvmentioning
confidence: 60%
See 3 more Smart Citations